9th LICMAS-2025 Book of Abstracts - Conference Scientific Committee (AlQalam Journal of Medical and Applied Sciences, 2025)
This is a collection of abstracts that was submitted for participation in the 9th Libyan International Conference on Medical, Applied, and Social Sciences held by the University of Tripoli Alahlia on July 12, 2025.